Pembuatan Sound Reactive LED Pada Dancer LED Clothes Menggunakan Arduino - Yoga Alif Utama; Tamaji Tamaji; Ulul Ilmi (Universitas Islam Lamongan, 2021)
Dance and music are an integral part of a dance performance. Along with the development of the era, dance is not only presented with dancer clothes with certain designs according to the flow and theme of a dance. However, the dancer clothes used are added with a series of LED lights as an attraction for entertainment offerings. The use of LED lights is intended to save power and be practical in terms of shape and size and have economic value. The LED lights that are used are also of various kinds, both LED strips, RGB LEDs, LED diodes and fiber optics according to the needs of dance performances.To create dance performances, dancer clothes will be designed that can interact directly with music. Where music is a parameter that will be used to turn on the LED light. This is an application that uses an automatic LED light controller to reduce the human error factor when the light is controlled by a remote.The controller is also equipped with Bluetooth as a means of sending information from cellphones or other gadgets or electronic devices that support the use of Bluetooth. Bluetooth pairing is intended so that clothes (dancer clothes) can run automatically without the use of cables and so that dancers can more freely when dancing. The results show that the tool can work properly, which can turn on, dim and turn off the lights according to the music being played. With this innovation, it is hoped that in the future it will further add to the LED dance creations that are currently developing in the entertainment world.